Development of cellular models expressing cynomolgus (Macaca fascicularis) HER2 for the functional evaluation of cross-reactive anti-human HER2 response - Cappello, Chiara; Ruzzi, Francesca; Consoli, Julia; Semprini, Maria Sofia; Scalambra, Laura; Pittino, Olga Maria; Angelicola, Stefania; Palladini, Arianna; Thorn, Mette; Nanni, Patrizia; Lollini, Pier-Luigi (Frontiers in Pharmacology, 2025)
IntroductionResistance to anti-HER2 therapies and incomplete response remain considerable challenges in managing HER2-positive tumors. Furthermore, some healthy organs, like the heart, express low levels of HER2, entailing a risk of toxic side effects, such as cardiotoxicity. Thus, the development of new anti-HER2 agents, to improve therapy outcomes, is still ongoing and requires preclinical evaluations of their side effects. Nonhuman primates are crucial in toxicology due to their high genetic similarity to humans. In line with the 3Rs principles, their use should be minimized by prioritizing the development of more predictive alternative methods. However, most in vitro assays (e.g., ELISA) only show the binding of anti-HER2 agents to cynomolgus HER2, without revealing the functional activities, such as growth inhibition.MethodsWe obtained cell lines expressing cynomolgus (Macaca fascicularis) HER2 (cyHER2), to evaluate the functional inhibitory activity of anti-human HER2 therapeutic agents on endogenous cynomolgus HER2 in three-dimensional (3D) growth condition in vitro.ResultsOur model, based on NIH 3T3 cells, became sensitive to the monoclonal antibody trastuzumab and to the selective HER2 tyrosine kinase inhibitor tucatinib.DiscussionThe results suggest that this model could be a promising tool for preclinical functional cross-reactivity tests of anti-HER2 therapies before in vivo studies.